Ensino e aprendizagem de função: uma metanálise de dissertações brasileiras sobre modelagem matemática produzidas entre 1987 e 2010 - Viana Filho, João Pereira (2012)
This has been written to investigate possible contributions of Mathematical modeling to teaching functions on Basic Education. In order to do this, investigations were aimed on answering the main question in the research: what are the contributions from researches which use Mathematical modeling, and what possibilities and difficulties come from this teaching and learning methodology or strategy to introduce or teach functions on both Ensino Fundamental (in Brazil it is from 1st grade to 9th grade) and Médio (10th to 12th grade)? A meta-analysis has been developed for this, and, in this case, we understand it according to Fiorentini and Lorenzato s (2009) proposal: a systematic review of other researches aiming to make a critical evaluation about them, with the intention of making a documental study, to summarize ideas, investigate contributions, classify and find research categories, find similarities and point possible differences or peculiarities between research results. The analysis has been done by following Severino s (2002) guidelines to reading, analyzing and interpreting texts, and it was conducted on seven Master s Degrees produced in Brazil, which have approached the theme learning and teaching functions with Mathematical modeling. Five of those are Professionalizing Masters (Mestrado Profissionalizante) and two of them are Academic Masters (Mestrado Acadêmico). Three of them are focused on Ensino Fundamental and four of them are focused on Ensino Médio. Those researches were found in and selected from the CAPES abstracts database. On research results, we present our identification and classifying criteria: eight categories for conception of Mathematical modeling, eight ways this can contribute to function teaching, six types of possibilities and five types of difficulties found on implementation and development activities and actions in the classroom, and six types of possible contributions that Mathematical modeling, when adopted as a function teaching and learning methodology or strategy in Ensino Fundamental and Médio, can bring. The results from the search and analysis of the theses have also pointed to the necessity of more research on themes related to the approach of functions in Basic Education (Educação Básica, from Preschool to 9th grade), using Mathematical modeling; specially Doctoral degrees (Doutorados)